Perception on climate change an exploratory study on urban citizens - Rahman, Muhammad Sabbir; Haque, Md. Mahmudul; Khan, Mohammad Bariul Karim (EuroJournals, Inc., 2011)
The purpose of this paper is to investigate to understand the urban citizens’ perception on climate change.Structural equation models were applied to test the propositions by means of a survey of a random sample of 300 general populations in Dhaka city of Bangladesh. This study explore that general citizens’ of Dhaka city feel that because of climate change the intensity of physical problem can be occurred with economic effects followed by psychological and environmental disorder. The outcome of this research shows a comprehensively integrated framework for academicians and policy makers to understand the vibrant relationships among several dimensions to have handful ideas on the climate change and its worse full effect on country like Bangladesh. However, researchers still predict that further research efforts are being needed to examine these factors in rural and urban area with additional samples before generalization can be made. Previous research related to the climate change and its effect on Bangladesh is mostly conceptual based on secondary data. This study explores the general citizens’ perception on climate change and its effects in physical, psychological, environmental and economic perspectives.